The Constitutional Role of Independent Fiscal Institutions in the Eurozone. Issue 2 (March 2022) - Fasone, Cristina
Abstract: The new European economic governance has made the creation or reform of independent fiscal institutions (IFIs) compulsory, in particular for Eurozone countries. While these institutions have been subject to extensive investigation by the economic literature, a constitutional analysis of their prospective and actual impact on national legal systems is lacking. In fact, depending on their design and powers, they could alter the ordinary inter-institutional dynamics on budgetary decisions. IFIs could redress the marginalization of parliaments in budgetary procedures in so far as they are able to offer reliable and independent information from the executive, and should mechanisms of "comply or explain" be put in place. By contrast, in the event an IFI operates within the executive branch and is not autonomous in the exercise of its mandate, parliamentary accountability could be further jeopardized. IFIs could also affect democratic rule-making over the budget, should their technocratic determinations be able to replace those of the budgetary authorities. Through a comparative constitutional analysis and based on selected case studies—France, Italy, Spain, and the Netherlands—the article aims to assess the constitutional impact of IFIs on parliaments and on the problem of information asymmetry on the budget.